Biodegradation of biopolymeric composites and blends under different environmental conditions: Approach towards end-of-life panacea for crop sustainability. (September 2021) - Kalita, Naba Kumar; Hazarika, Doli; Kalamdhad, Ajay; Katiyar, Vimal
Abstract: This study reports the biodegradation behaviour of polylactic acid (PLA) based biocomposites under three different types of compost. In order to check its biodegradability under natural outdoor soil condition another study was designed comprising of PLA and compared with polycaprolactone (PCL) based biocomposites and polyblends containing fillers like wood-dust, algal biomass and microcrystalline cellulose (MCC). Under thermophilic composting conditions, it was found that neat PLA samples took around 95-110 days to degrade. For outdoor (uncontrolled) degradation, natural soil available was selected for the test and samples were buried 20 cm deep. After bioplastic biodegradation under composting condition the final biomass formed was used to evaluate its ecotoxicological impact on crop ( Solanum tuberosum L ) growth following OECD 2006 test guidelines. This study revealed current understanding to spot the data gaps and future analysis priorities related to final biomass of bioplastic biodegradation as well as biopolymer's tremendous role in "nature-to-nature" sustainability. Graphical abstract: Unlabelled Image Highlights: Biodegradation of NPLA was studied under three different compost type. PCL was found to be degradable under natural outdoor soil condition. The study showed ecotoxicological effect of biopolymers on plant growth. Ecotoxicological study was conducted under controlled greenhouse conditions. Bioplastics microparticles had no negative effect on the crop growth.